A Human-Centered Approach to One-Shot Gesture Learning - Cabrera, Maria Eugenia; Wachs, Juan Pablo (Frontiers in Robotics and AI, 2017)
This paper discusses the problem of one-shot gesture recognition using a human-centered approach and its potential application to fields such as human-robot interaction where the user’s intentions are indicated through spontaneous gesturing (one-shot). Casual users have limited time to learn the gestures interface, which makes one-shot recognition an attractive alternative to interface customization. In the aim of natural interaction with machines, a framework must be developed to include the ability of humans to understand gestures from a single observation. Previous approaches to one-shot gesture recognition have relied heavily on statistical and data-mining-based solutions, and have ignored the mechanisms that are used by humans to perceive and execute gestures and that can provide valuable context information. This omission has led to suboptimal solutions. The focus of this work is on the process that leads to the realization of a gesture, rather than on the gesture itself. In this case, context involves the way in which humans produce gestures—the kinematic and anthropometric characteristics. In the method presented here, the strategy is to generate a data set of realistic samples based on features extracted from a single gesture sample. These features, called the “gist of a gesture,” are considered to represent what humans remember when seeing a gesture and, later, the cognitive process involved when trying to replicate it. By adding meaningful variability to these features, a large training data set is created while preserving the fundamental structure of the original gesture. The availability of a large data set of realistic samples allows the use of training classifiers for future recognition. The performance of the method is evaluated using different lexicons, and its efficiency is compared with that of traditional N-shot learning approaches. The strength of the approach is further illustrated through human and machine recognition of gestures performed by a dual arm-robotic platform.